Penerapan teknik assertive training dalam mereduksi konformitas negatif terhadap kelompok sebaya di SMP - selfi selfi (Universitas Negeri Makassar, 2017)
The objectives of the research (1) the implementation of assertive training technique in reducing negative conformities toward peer group, (2) the students negative conformities before and after being given assertive training technique, (3) assertive training technique in reducing negative conformities toward peer group. The research employed quantitative approach by using true experimental design with pretest-postest control group design. The subjects of the research were 22 students of class IX who were identified they had high negative conformities toward peers. Thw data collection technique employed negative conformitas scale, observation, and interview. The results of the research reveal that (1) the implementation of assertive training technique in reducing negative conformities toward peer group is implemented based on the procedure designed in 5 meetings, (2) negative conformities towards peer group before the implementation of assertive training technique is in high category. However, after the implementation of assertive training technique, peer group is in low category, (3) the implementation of assertive training technique in reducing negative conformities toward peer group at SMPN 1 Sungguminasa, meaning that the students who were given the implementation of assertive training technique showed the reduction of negative conformities toward peer